2000
DOI: 10.1128/jvi.74.5.2351-2364.2000
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Cell Leukemia Virus Type 1 Tax Shuttles between Functionally Discrete Subcellular Targets

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) Tax is a nuclear protein with striking pleiotropic functionality. We recently demonstrated that Tax localizes to a multicomponent nuclear speckled structure (Tax speckled structure [TSS]). Here, we examine these structures further and identify a partial overlap of TSS with transcription hot spots. We used a strategy of directed expression via fusion proteins to determine if these transcription sites are the subtargets within TSS required for Tax function. When fused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 60 publications
6
70
0
Order By: Relevance
“…In this respect it appears that subcellular localization of the viral protein Tax would be an effective means of regulating virus-cell interactions. We previously reported that Tax can shuttle between the nucleus and cytoplasm (30) and would favor a model ascribing control of overall Tax function via regulation of targeting to subnuclear sites. Uncovering the mechanism by which Tax targets to multiple subcellular sites would help explain the pleiotropic functionality of this protein.…”
Section: Figmentioning
confidence: 99%
“…In this respect it appears that subcellular localization of the viral protein Tax would be an effective means of regulating virus-cell interactions. We previously reported that Tax can shuttle between the nucleus and cytoplasm (30) and would favor a model ascribing control of overall Tax function via regulation of targeting to subnuclear sites. Uncovering the mechanism by which Tax targets to multiple subcellular sites would help explain the pleiotropic functionality of this protein.…”
Section: Figmentioning
confidence: 99%
“…Spot 30 in panel A and small arrows in panel B and C are tropomyosin and were used as an internal standard control. D, typical MALDI-TOF mass spectra of in-gel digested sample spots (1,2,4,6,7,16,19, and 25) from 2-D PAGE. Star-labeled peaks of each spectrum (Table I) are peptides matched for specific protein candidates found in the data base.…”
Section: Fig 2 Two-dimensional Electrophoresis Pattern Of the Tax 1mentioning
confidence: 99%
“…CREB-dependent) and cytoplasmic (e.g. NFB-dependent) levels, functioning through shuttling proteins between these two compartments (2,3).…”
mentioning
confidence: 99%
“…Specifically, with respect to the regulation of multiple Tax activities, it has been noted that mutation or deletion of individual domains results in a selective loss of function (13). Important domains for Tax function include a nuclear localization signal (13,14), nuclear export signal (15,16), activation specific region (17), two leucine zip-like domains (18,19), and a zinc-finger domain (20). Mutation of a number of individual serine residues in Tax have been shown to alter its ability to trans-activate either CREB or NF-B-responsive promoters (13).…”
mentioning
confidence: 99%